Menghidupkan Semula Etika dan Nilai-nilai Murni Demokrasi dalam Konteks Autonomi Negeri: Kes Indonesia - Al-Muchtar, Suwarma; Suwirta, Andi (ASPENSI in Bandung, Indonesia, 2008)
ABSTRACT: This paper discusses the vision of democracy, the various efforts to enlighten the ethics and good values in practicing democracy, especially in the relation to the current multi-dimensional political crises currently faced by the Indonesians after the 1998 Reformation movement until today. The realization of the Regional Autonomy Act in 1999 had however directly been reducing the authority of Central Government in Indonesia. This had significantly been worrying the existence of national integration. The emergence of many crises after 1997 had caused very bad social conflict be it horizontally or vertically, where at the end had jeopardized the living of Indonesians. Realizing the thinking and practicing the good values of democracy in the context of political culture of Indonesia is being viewed by this working paper as important especially to the government and the people in practicing the âRechstaatsâ vision and diminishing the âMachstaatsâ. Therefore, exemplary governmental leadership, upholding legal correctness and justice and continuous learning and teaching process of good values in moral education, civic and law will be part of the suggestion in this paper. Key words:Â ethical concept and good values, regional autonomy act, democracy education and the role of social science and humanity scholars.Â Â About the Authors: Prof. Dr. Suwarma Al-Muchtar adalah Profesor Pengajian Sosial dan Dekan Fakulti Pendidikan Sains Sosial UPI (Universiti Pendidikan Indonesia) di Bandung. Beliau lahir di Garut, Jawa Barat, pada 11hb Februari 1953. Menamatkan Program Dr. Pendidikan IPS di Sekolah Pascasiswazah IKIP Bandung tahun 1995. Menulis buku, di antaranya adalah Pengantar Studi Sistem Politik Indonesia (Bandung: Gelar Pustaka Mandiri, 2001). Beliau boleh dihubungi dengan alamat jabatan: Fakulti Pendidikan Ilmu Pengetahuan Sosial UPI, Jl.Dr. Setiabudhi No.229 Bandung 40154, Jawa Barat, Indonesia. E-mail: sam@upi.edu Andi Suwirta, M.Hum. adalah Pensyarah Kanan di Jabatan Pendidikan Sejarah FPIPS UPI. Beliau dilahirkan di Subang, Jawa Barat, pada 9hb Oktober 1962. Menamatkan Sarjana (M.Hum.) dari Program Pengajian Ilmu Sejarah Pascasiswazah UI (Universiti Indonesia) Jakarta tahun 1996, dengan menulis tesis masternya, dan diterbitkan, mengenai Suara dari Dua Kota: Revolusi Indonesia dalam Pandangan Suratkabar Merdeka (Jakarta) dan Kedaulatan Rakjat (Yogyakarta), 1945-1947 (Jakarta: PN Balai Pustaka, 2000). Beliau boleh dihubungi dengan alamat: Komp. Vijaya Kusuma B-11 No.15-16 Cipadung, Bandung 40614, Jawa Barat, Indonesia. E-mail: suciandi@upi.eduHow to cite this article? Al-Muchtar, Suwarma & Andi Suwirta. (2008). âMenghidupkan Semula Etika dan Nilai-nilai Murni Demokrasi dalam Konteks Autonomi Negeri: Kes Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.1 [Mei]. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112, pp.27-48.Chronicle of the article: Accepted (March 24, 2008); Revised (April 29, 2008); and Published (May 20, 2008).